Korelasi antara asupan cairan, kalium, natrium dengan interdialytic weight gain pada pasien hemodialisis rutin - Nabilah, Defa Nuzul; Ningsih, Windi Indah Fajar; Flora, Rostika; Ramdika, Sari Bema (Jurnal Gizi Klinik Indonesia, 2025)
Correlation between fluid intake, potassium, sodium, and interdialytic weight gain (IDWG) in routine hemodialysis patientsBackground: Chronic kidney failure patients undergo hemodialysis regularly to help kidney function. One of the problems that often occurs in patients with chronic kidney failure when undergoing hemodialysis is an increase in interdialytic weight gain (IDWG).Objective: This study aims to determine the correlation between fluid, potassium, and sodium intake with IDWG in hemodialysis patients at RSUP Dr. Mohammad Husein Palembang.Method: This study employs a quantitative approach with a cross-sectional design. The sampling technique used was purposive sampling, resulting in 62 respondents who met the inclusion and exclusion criteria. The data collected included the characteristics of the respondents, as assessed through a questionnaire. Additionally, data on fluid, potassium, and sodium intake were collected using a 2x24-hour food recall form. Body weight data were measured before and after hemodialysis using digital scales. Bivariate analysis was carried out using the Spearman correlation test.Results: There was a significant correlation between fluid intake (p-value = 0.022) and sodium intake (p-value = 0.049) with IDWG, with a positive correlation direction, indicating a relationship in the same direction. The correlation was sufficient for fluids with IDWG, but weaker for sodium with IDWG. There was no relationship between potassium intake (p-value = 0.062) and IDWG.Conclusions: The unexpected increase in IDWG in hemodialysis patients is related to fluid and sodium intake; therefore, the higher the sodium and fluid intake, the greater the increase in IDWG.